Evaluation of the Implementation of Community-Based Water Supply and Sanitation Programs in Cihara Village, Lebak Regency - Dianingsih, Dini Ulfah; Yulianti, Rina; Waseh, Hasuri (Jurnal Magister Administrasi Publik, 2021)
This study aims to evaluate the implementation of Community Based Drinking Water and Sanitation Provision III in Cihara Village, Cihara District, Lebak Regency. The theory used is the evaluation theory by Dunn (2003: 610), namely effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The method used is descriptive with a qualitative approach. The result of this research is that the implementation of the PAMSIMAS III program in Cihara Village, Cihara District, Lebak Regency has not run optimally. Suggestions that become recommendations for supervision from related agencies after the construction of facilities is complete and there are efforts from related agencies to provide awareness to the community about the importance of PHBS, community self-help groups have strategies so that people can participate in the form of in-cash contributions and in deliberations, and the existence of cross subsidies for infrastructure maintenance fees for people who are economically underprivileged.